Flexibility as Risk Management Option Implemented in the Bridge Repair - Jerzy Paslawski (The Baltic Journal of Road and Bridge Engineering, 2011)
Risk management in the sphere of Construction Management concentrates, on principle, at the level of projects or organizations which coordinate them. The construction business, however, when compared to many other branches of industry, is characterized by considerable operational risk. Therefore it seems that a direct impact on risk through implementation of flexibility with the proactiveness priority taken into account at the operational (source) level is a unique chance for successful risk management in the construction process engineering. The flexibility is understood in this case as the ability of an organization executing construction processes to adjust to dynamically changing environment through preparation of alternative variants (options), easy to switch over to. The specific character of implementation of flexibility has been illustrated with an example of repairing a road construction structure, with dissimilarity of that application to typical situations being emphasized.